Impact of COVID-19 Pandemic on Consumer Behavior towards the Intention to Use E-Wallet in Malaysia - Friday Ogbu Edeh; Dwi Nita Aryani; Tanuja A/P Subramaniam; Daisy Mui Hung Kee; Tejas Samarth; Rajesh Kumar Nair; Thirumagal A/P Kannappan; Yee Shan Tan; Yi Ching Teh (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2021)
The technology-driven era has encouraged Malaysians to use e-Wallet rather than paper money in their daily transactions. Numerous e-Wallet applications have been developed, such as GrabPay, Touch 'n Go eWallet, and Boost. Erstwhile, Malaysians perceived that using e-Wallets is troublesome and worthless. However, the COVID-19 outbreak has reframed the buyers' perceptions otherwise. This study investigates the impact of Covid-19 on consumer behavior towards the intention to use e-Wallet in Malaysia. A sample of 100 Malaysians has voluntarily participated in this survey. Data were assembled through an electronic survey questionnaire. Contrary to popular belief, the findings depicted that the behavioral intention to use e-Wallets among Malaysians had further accelerated due to the convenience perceptions, facilitating conditions, and perceived safety.